2019
DOI: 10.1111/birt.12420
|View full text |Cite
|
Sign up to set email alerts
|

Hospital‐based maternity care practitioners’ perceptions of doulas

Abstract: Introduction A birth doula provides continuous informational, physical, and emotional support during pregnancy, labor, and immediately postpartum. Existing data on the benefits of doulas, especially for low‐resource, high‐need patients, do not address how and why individual practitioners decide to recommend this model of care. This project aims to describe best practices of integrating doulas into hospital‐based maternity care teams to facilitate access to this evidence‐based service for improving maternal hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
0
25
1
Order By: Relevance
“…Previous research has shown that clinicians may have negative perceptions of doulas if they have experiences interacting with them in an adversarial manner. 41 , 42 A recent survey of maternity care clinicians suggested that educating clinicians about doulas' training and creating clear guidelines for the role of doulas within the maternity care team could foster positive doula–clinician relationships. 41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that clinicians may have negative perceptions of doulas if they have experiences interacting with them in an adversarial manner. 41 , 42 A recent survey of maternity care clinicians suggested that educating clinicians about doulas' training and creating clear guidelines for the role of doulas within the maternity care team could foster positive doula–clinician relationships. 41 …”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 A recent survey of maternity care clinicians suggested that educating clinicians about doulas' training and creating clear guidelines for the role of doulas within the maternity care team could foster positive doula–clinician relationships. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Colombia and other countries with communities experiencing health disparities ought to make Doulaism widespread and accessible, aimed to improve pregnancy outcomes and other woman-related indicators in clinical settings. Importantly, the inclusion of doulas into the formal health system and childbirth education must be done gradually and with constant discussion with health-care providers to avoid those confrontations described by L as well as reported in other countries and settings with health disparities (Lucas & Wright, 2019;Neel et al, 2019). Considering that doulas provide interventions focused on companionship to promote the emotional well-being of pregnant women, childbirth educators can learn from them with the aim of seeking the humanization of a health-care system that historically has diminished and violated women's sexual and reproductive rights.…”
Section: Discussion and Practice Implicationsmentioning
confidence: 99%
“…Every pregnant woman accessing services was provided a doula to support her during and after her pregnancy. Neel, Goldman, Marte, Bello, and Nothnagle (2019) described a doula as a trained healthcare professional who offers information and emotional and physical support, before, during, and after pregnancy; doula is also defined under the definitions of terms section. The experience of providing doulas to support pregnant Indigenous women has stuck with me, as it highlighted positive social work practice and demonstrated that the child welfare system can implement creative and preventative measures.…”
Section: Informing This Researchmentioning
confidence: 99%
“…This means that the director of child welfare gives his or her authority to social workers to be able to enact the CFCSA. -Neel et al, (2019) describe a doula as a trained health worker who "provides continuous informational, physical, and emotional support during pregnancy, labor, and immediately postpartum" (p. 355). The involvement of a doula can have numerous positive outcomes including, higher breastfeeding rates and more satisfying birth experiences (Neel et al, 2019).…”
Section: Bond(ing) -mentioning
confidence: 99%